Modelo de avaliação de desempenho logístico de empresa de serviço - Alves, Vanessa Teresinha (2012)
There is a consensus among researchers and practitioners that logistics plays a strategic role, regardless of the activity or sector in which the organization operates. This reputation is due to the web of interrelations involved and the scope of their actions. However, in this global context, numerous elements, the logistics focus of this study is presented as a pillar of support and integration link of the chain. Research focusing on the assessment of logistics performance in service companies are scarce, which is a gap to be filled. Most of the jobs found are directed to review the logistics companies in manufacturing and service level considering only the vision of the client (from the outside) and not aspects that focus within the organization. Based on this gap, we present the research problem: how to evaluate logistics performance in a service company? With the intention of finding alternatives to the problem was indispensable study on the subject using theoretical basis of the survey on the industry besides defining the basis for reasoning model and identification of submerged logistics processes. It was essential to the description of the methodology of multicriteria constructivist-MCDA-C, as this was used as the basis for the model to be proposed. To this end, we proceeded with a systematic search of mapping the current situation based on the variables identified, allowing opportunities for streamlining processes, providing a vision of the future state and to guarantee the sustainability of suggested actions. Aiming to solidify and test the model, we used the procedure with case study application in a company providing telecommunications services which operates in three Brazilian states, where it became possible to evaluate the performance of logistics, respecting the variables identified enabling the assessment be observed each individual case and its coverage globally. In this format, the proposed model seeks to provide conditions for the company to monitor the performance of their actions, maintaining indexes for goal setting and periodic evaluations of individual and collective performance. The proposed model proved to be suitable for providing a tool where there is a systematic process of continuous improvement with a focus on integration and advancement of logistics performance solidified.